Therapy of older persons with acute myeloid leukaemia - Krug, Utz; Müller-Tidow, Carsten (Leukemia research, 2017)
Most persons age≥60 y with acute myeloid leukaemia (AML) die from their disease. When interpreting clinical trials data from these persons one must be aware of substantial selection biases. Randomized trials of post-remission treatments can be performed upfront or after achieving defined landmarks. Both strategies have important limitations. Selection of the appropriate treatment is critical. Age, performance score, co-morbidities and frailty provide useful data to treatment selection. If an intensive remission induction therapy is appropriate, therapy with cytarabine and an anthracycline is the most common regimen. Non-intensive therapies consist of the hypo-methylating drugs azacitidine and decitabine, low-dose cytarabine and supportive care. Feasibility of doing an allotransplant in older persons with AML is increasing. However, only very few qualify. Results of cytogenetic testing are risk factor in young and old persons with AML. Adverse abnormalities are more frequent in older persons. Although data about the frequency of mutations in older persons with AML is increasing their prognostic impact is less clear than in younger subjects. Neither differences in the distribution of cytogenetic risk, mutations, nor differences in clinical risk factors between younger and older persons with AML completely explain the age-dependent outcome. Many drugs are in clinical development in older persons with AML. Their potential role in the treatment of older persons with AML remains to be defined.